2022
DOI: 10.3390/jof8020094
|View full text |Cite
|
Sign up to set email alerts
|

Native Rhizospheric and Endophytic Fungi as Sustainable Sources of Plant Growth Promoting Traits to Improve Wheat Growth under Low Nitrogen Input

Abstract: Wheat crops require effective nitrogen fertilization to produce high yields. Only half of chemical N2 fertilizers are absorbed into plants while the rest remains in the soil, causing environmental problems. Fungi could maximize nitrogen absorption, and from an environmental and biodiversity point of view, there is an urgent necessity for bioprospecting native fungi associated with wild plants growing in harsh environments, e.g., St. Katherine Protectorate (SKP) in the arid Sinai. Recovered taxa, either endophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…Therefore, PGP substance properties are more important than the efficient production of siderophores. These results are consistent with Mohamed et al [ 58 ], who showed that P. chrysogenum NGB-WFS2, which could highly solubilize phosphorus and IAA production, while having a low percentage of siderophore production, could promote plant growth better than A. versicolor NGB-WFS9, which could produce a high amount of siderophores. However, it was found that chemical fertilizers were more effective in promoting some characteristics of Maled Phai rice than endophytes.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, PGP substance properties are more important than the efficient production of siderophores. These results are consistent with Mohamed et al [ 58 ], who showed that P. chrysogenum NGB-WFS2, which could highly solubilize phosphorus and IAA production, while having a low percentage of siderophore production, could promote plant growth better than A. versicolor NGB-WFS9, which could produce a high amount of siderophores. However, it was found that chemical fertilizers were more effective in promoting some characteristics of Maled Phai rice than endophytes.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the phosphorus present in the soil can be found in the form of phosphates, which form compounds together with metals, minerals (inorganic substances), and organic materials (organic substances) [91]. Although P is abundantly found in agricultural soils, most of it is present in its insoluble form; thus, it cannot be directly used by plants [92]. Consequently, to achieve an optimal crop yield, synthetic fertilisers with P are used; however, only approximately 30% of the added P can be used by crops as a large portion of the P remains immobilised in the form of insoluble phosphate or migrates in the soil [93].…”
Section: Implications Of Dses In Fertilisation Reductionmentioning
confidence: 99%
“…This increased Fe intake may be related to the ability of endophytic microorganisms to produce siderophores under limiting iron stress conditions [125][126][127]. Moreover, these siderophores produced by endophytes tend to have more affinity for Fe 3+ ions than the phytosiderophores produced by plants [92]. P. fortinii is capable of synthetising hydroxamate siderophore, and such synthesis has been linked to the increased incorporation of Fe 3+ by the host plant [124].…”
Section: Implications Of Dses In Fertilisation Reductionmentioning
confidence: 99%
“…These fungi synthesize a wealth of functional metabolites like alkaloids, terpenoids, amines, flavonoids, steroids, and phenolic compounds (Ding et al 2008). Notably, they are recognized for their production of novel antimicrobial agents, anticancer compounds such as Taxol, and industrially valuable enzymes (Salem & Abdel-Azeem 2014;Netala et al, 2016;Mohamed et al 2022;Moubasher et al 2022).…”
Section: Introductionmentioning
confidence: 99%